Pengaruh Model Project Based Learning dengan Pendekatan Realistic Mathematics Education terhadap Kemampuan Numerasi Siswa - Lutfatul Hasanah; Isnaini Nur Azizah; Choirudin Choirudin (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2026)
This study aims to analyze the effect of the Project based learning (PjBL) model integrated with the Realistic Mathematics Education (RME) approach on students’ numeracy skills in social arithmetic material. The study uses a quantitative approach with a quasi-experimental design of the NonEquivalent Control Group Design type. The research population is from one private senior high school in Metro City. The sample consists of 44 eleventh-grade students divided into an experimental class and a control class, each consisting of 22 students. The research instrument is a multiple-choice numeracy test that has met the criteria of validity and reliability. Data analysis is conducted through the Shapiro–Wilk normality test, Levene’s homogeneity test, and the Independent Sample t-test at a significance level of 0.05. The results of the study show a significant difference between the experimental and control classes (t(42) = −3.737; p = 0.001). The N-Gain score of the experimental class is 0.557 (moderate category), which is higher than the control class at 0.278 (low category). It is concluded that the integration of PjBL and RME is effective in improving students’ numeracy skills and can be used as an alternative contextual and meaningful mathematics learning approach.